Preliminary Study on Antibacterial Activity of Sawo Kecik (Manilkara kauki (L.) Dubard) Roots Extract - Novida Pratiwi; Rini Retnosari; Sitoresmi Prabaningtyas (UIN Sunan Gunung Djati Bandung, 2021)
The roots of sawo kecik (Manilkara kauki (L.) Dubard) contain astringent that can be used to treat diarrhea for infants. However, the active antibacterial substance in sawo kecik roots has not been known. Therefore, the research to understand the antimicrobial activity of sawo kecik roots extract against Escherichia coli and Staphylococcus aureus was performed. Sawo kecik roots were macerated using methanol and chloroform. The result was then treated with E.coli and S.aureus with a concentration of 5 ppm and compared to negative control (solvent) and further observed and analyzed how reduced the bacterial growth with Two Ways ANOVA without interaction. The research results indicated that the sawo kecik roots methanol extract was effective to slow down the growth of S.aureus (0.160 ± 0.007) but ineffective against E.coli, whereas sawo kecik roots chloroform extract was not effective to reduce both bacteria. It can be concluded that further research is required to measure and verify the antibacterial activity of the extract using higher concentration samples and different research methodology.